ANALISIS KEBUTUHAN TENAGA REKAM MEDIS MENGGUNAKAN METODE WORKLOAD INDICATOR STAFF NEED (WISN) DI UPTD PUSKESMAS WERU TAHUN 2020 - Wahyu Ningsih, Sri; Hakam, Fahmi; Asriati, Yul (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2020)
The Workload Indicator Staff Need (WISN)is an indicator that shows the amount of staffneeded at health facilities based on workload, so that location or relocation will be easier andmore rational. There is medical record officer at the UPTD health center Weru in the outpatientregistration section who continues his education so that in his work duties must be replaced byofficers in the filing division. Filing officers concurrently have duties as registration officers.Cause the workload of officers is high and officers in carrying out their duties are not inaccordance with the established SOP. The purpose of this study was to calculate availableworking time, workload standards, allowance standards and the need for medical record personelat the UPTD health center Weru. This type of research is a descriptive study with a cross sectionalapproach.. The subjects in this study were 3 medical record staff and the object was the medicalrecord staff. Data collection was carried out by observation and interviews with medical recordofficers at the UPTD health center Weru. The research instrument was an observation cheklist andinterview guidelines.The calculation is done using the WISN method. It is known that the availableworking time is 1,925 hours / year or 115,500 minutes / year, the need for the workload foroutpatient registration is 452,375 minutes, the filing section is 2.749.542 minutes, the inpatientregistration section or the emergency room is 420,063 minutes. The standard calculation ofallowance is 0.15 hours / year, the calculation of the need for personnel is 5 personnel, so it isnecessary to add 1 officer in the outpatient registration section of the UPTD healt center Werut.